2010
DOI: 10.4049/jimmunol.0902711
|View full text |Cite
|
Sign up to set email alerts
|

CD22 × Siglec-G Double-Deficient Mice Have Massively Increased B1 Cell Numbers and Develop Systemic Autoimmunity

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
148
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 129 publications
(153 citation statements)
references
References 51 publications
3
148
1
1
Order By: Relevance
“…These findings are of importance and explain the mechanism of the inhibitory receptor Siglec-G in the mouse and potentially also its counterpart in the human, Siglec-10. Both CD22 and Siglec-G have been shown to be involved in B cell tolerance induction (11), and a deficiency in both of these receptors together leads to autoimmunity (22). Our findings are therefore highly relevant for the better understanding of B cell-driven autoimmune diseases and offer new treatment concepts for patients with these diseases.…”
Section: Discussionmentioning
confidence: 93%
“…These findings are of importance and explain the mechanism of the inhibitory receptor Siglec-G in the mouse and potentially also its counterpart in the human, Siglec-10. Both CD22 and Siglec-G have been shown to be involved in B cell tolerance induction (11), and a deficiency in both of these receptors together leads to autoimmunity (22). Our findings are therefore highly relevant for the better understanding of B cell-driven autoimmune diseases and offer new treatment concepts for patients with these diseases.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, it is possible that bone marrow progenitors play a larger role in NOD B1a cell ontogeny, conditioning a higher B220 expression. Additionally, increased B220 expression is associated with a lower threshold of activation [38,39] and possibly underlies the surface immunophenotypes observed in NOD peritoneal B1a cells. This B1a B cell surface profile was also observed in male NOD mice, strengthening the suggestion that such NOD phenotypes are genetically determined and not affected by the degree of beta cell destruction (ESM Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is different on a mixed 129 × C57BL/6 background (23) or when CD22 −/− mice are crossed to Siglec-G −/− mice, which suggests some redundancy, as Siglec-G is a similar inhibitory receptor on B cells (3). One study showed that mice with a mutated CD22 ligand-binding domain had similar phenotypes to the CD22-deficient mice, without affecting Ca 2+ signaling.…”
mentioning
confidence: 99%
“…How ligand recognition of the Siglecs is mechanistically linked to the inhibitory function of these molecules is not clear. Loss of both CD22 and Siglec-G in B cells leads to spontaneous autoimmunity in mice (3). Additionally, mutations in an acetyl sialic acid esterase gene, coding for an enzyme, which modifies Siglec ligands, lead to autoimmunity (4).…”
mentioning
confidence: 99%